2021
DOI: 10.3389/fmicb.2021.685224
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profiling of Rhizobacteria Serratia plymuthica and Bacillus subtilis Revealed Intra- and Interspecific Differences and Elicitation of Plipastatins and Short Peptides Due to Co-cultivation

Abstract: Rhizobacteria live in diverse and dynamic communities having a high impact on plant growth and development. Due to the complexity of the microbial communities and the difficult accessibility of the rhizosphere, investigations of interactive processes within this bacterial network are challenging. In order to better understand causal relationships between individual members of the microbial community of plants, we started to investigate the inter- and intraspecific interaction potential of three rhizobacteria, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 85 publications
(107 reference statements)
0
6
0
Order By: Relevance
“…This lipopeptide has a peptide moiety of two amino acid residues (i.e., Ser-Ser) linked to two C 10 fatty acid chains ( Figure 1A ) ( Matsuyama et al, 1985 ). Numerous analogues of this compound have been identified, which are produced by pigmented and non-pigmented S. marcescens, S. ureilytica, and S. plymuthica strains (as well as a Serratia liquefaciens strain that was reclassified as a S. marcescens strain), that vary based on the length and saturation/unsaturation of the fatty acid moiety and can be cyclic or open-ring structures ( Eberl et al, 1999 ; Labbate et al, 2007 ; Dwivedi et al, 2008 ; Kuo et al, 2012 ; Clements et al, 2021 ; Menezes et al, 2021 ). Serratamolides exhibit promising activity against Gram-positive bacteria, such as Enterococcus faecalis , Mycobacterium spp.…”
Section: Antimicrobial Lipopeptides: Production By Underexplored Bact...mentioning
confidence: 99%
See 1 more Smart Citation
“…This lipopeptide has a peptide moiety of two amino acid residues (i.e., Ser-Ser) linked to two C 10 fatty acid chains ( Figure 1A ) ( Matsuyama et al, 1985 ). Numerous analogues of this compound have been identified, which are produced by pigmented and non-pigmented S. marcescens, S. ureilytica, and S. plymuthica strains (as well as a Serratia liquefaciens strain that was reclassified as a S. marcescens strain), that vary based on the length and saturation/unsaturation of the fatty acid moiety and can be cyclic or open-ring structures ( Eberl et al, 1999 ; Labbate et al, 2007 ; Dwivedi et al, 2008 ; Kuo et al, 2012 ; Clements et al, 2021 ; Menezes et al, 2021 ). Serratamolides exhibit promising activity against Gram-positive bacteria, such as Enterococcus faecalis , Mycobacterium spp.…”
Section: Antimicrobial Lipopeptides: Production By Underexplored Bact...mentioning
confidence: 99%
“…Recently, several bacterial genera such as Serratia , Brevibacillus and Burkholderia , have emerged as underexplored sources of novel antimicrobial lipopeptides ( Etzbach et al, 2014 ; Burgard et al, 2017 ; Ganley et al, 2018 ; Li et al, 2018 ; Sang et al, 2019 ; Ning et al, 2021 ). For example, four species within the Serratia genus, including Serratia marcescens ( S. marcescens ) , Serratia plymuthica ( S. plymuthica ) , Serratia ureilytica ( S. ureilytica ), and Serratia surfactantfaciens ( S. surfactantfaciens ), have been reported as lipopeptide producers, with serrawettin W1 (also referred to as serratamolide), serrawettin W2 or stephensiolides families, produced by various strains ( Kuo et al, 2012 ; Menezes et al, 2021 ; Clements-Decker et al, 2022 ). Strains of Brevibacillus laterosporus ( B. laterosporus ) and Brevibacillus brevis ( Br.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, some of the compounds involved in the antagonistic activities observed in dual cultures may not have been produced or produced only weakly. Indeed, it has been shown that resource competition and inter-and intraspecific microbial interactions are often implicated in the induction of the biosynthesis of antimicrobial compounds [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Data filtering was implemented by detecting and removing non-informative variables characterized by near-constant values throughout the experimental conditions by comparing their robust estimate interquartile ranges (IQR). Data was auto-scaled out of the 3020 mass features originally detected, using the Principal Least Square Discriminant Analysis PLS-DA [4] .…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%